Effect of anastomotic reinforcement with barded suture on anastomotic leakage prevention following laparoscopic low anterior resection for rectal cancer: a retrospective single-center study - Xinyu Qi; Kai Xu; Maoxing Liu; Fei Tan; Pin Gao; Chuanyong Zhou; Zhendan Yao; Nan Zhang; Hong Yang; Chenghai Zhang; Jiadi Xing; Ming Cui; et al. (BMC Surgery)
Abstract Background Anastomotic leakage (AL) is a serious complication that may occur following the double stapling technique (DST). The study aims to investigate the efficacy of anastomotic reinforcement using barbed sutures in preventing AL after laparoscopic low anterior resection (LAR) for rectal cancer. Methods During the period from November 1, 2018 to November 1, 2023, a total of 725 consecutive patients who had underwent laparoscopic LAR for rectal cancer were enrolled in this study. The patients were divided into two groups: the continuous barbed suture reinforcement group (N = 296) and the control group (N = 429). Inter-group comparisons were used the chi-squared test, Fisher’s exact test, and nonparametric tests. Independent risk or protective factors for AL were analyzed using the multivariate logistic regression. Results Among the 725 patients enrolled in this study, 24 patients (3.3%) were diagnosed with AL following surgery. The incidence of AL was lower in the reinforcement group when compared with the control group (1.4% vs. 4.7%, P = 0.014). In multivariate regression analyses, the neoadjuvant therapy (OR = 11.994, P < 0.01), tumor location (OR = 5.306, P = 0.015), anastomosis bleeding (OR = 58.822, P < 0.01), and number of staple firings used (≥ 3) (OR = 24.752, P < 0.01) were independent risk factors for AL, whereas the defunctioning stoma (OR = 0.051, P < 0.01) and reinforcing sutures (OR = 0.054, P = 0.001) were independent protective factors for AL in this study. No statistically significant differences were found in 36-item short-Form (SF-36) when evaluating the quality of patient’s life between the two groups. Conclusions Laparoscopic continuous barbed suture reinforcement of anastomosis could reduce the incidence of AL without affecting the quality-of-life following LAR. Further popularization of this approach in clinical is warranted. Trial registration Retrospectively registered.